Design and Development of Robotic Arms: Structural Innovation, Intelligent Control, and Application Expansion - Dong, Qiyu (Exploring Science Academic Conference Series, 2026)
Robotic arms, as core executive components of industrial automation and intelligent robotics, are widely applied in industrial manufacturing, agricultural picking, medical rehabilitation, aerospace, and other fields. This paper systematically reviews the development history and current research status of robotic arms, focusing on structural design innovations, including rigid -flexible switching, bionic configurations, and lightweight materials, as well as intelligent control technologies, such as adaptive c ontrol, machine vision fusion, and human-machine interaction. The key technical bottlenecks that restrict the development of robotic arms are analyzed, including the trade -off between lightweight design and high load capacity, accuracy errors due to flexible deformation, poor adaptability in unstructured environments, and high operational costs. Finally, the future development trends of robotic arms are predicted to center on bionic integration, intelligent collaboration, modular customization, and green, energy-saving technologies, thereby providing a theoretical reference and technical support for subsequent research and engineering applications.